Back back Cover: Chemical Weathering of Alumina in Aqueous Suspension at Ambient Pressure: A Mechanistic Study (ChemCatChem 12/2017). Issue 12 (22nd June 2017) - Abi Aad, Jane; Casale, Sandra; Michau, Mathieu; Courty, Philippe; Diehl, Fabrice; Marceau, Eric; Carrier, Xavier
Abstract : The Front Cover depicts the degradation of transition aluminas used as supports for heterogeneous catalysis in heated aqueous suspensions. In their Full Paper, J. Abi Aad et al. demonstrate that all transition aluminas (from γ to θ‐Al2 O3 ) transform into Al(OH)3 polymorphs (bayerite, gibbsite, and nordstrandite) to different extents. The nature of the main polymorph is a function of aluminium concentration and ageing time. More information can be found in the Full Paper by J. Abi Aad et al. onpage 2186 in Issue 12, 2017 (DOI:10.1002/cctc.201700145 ).